The Role of the Integrating Factor in the Shaping of Transborder Co-Operation: The Case of Poland - Dołzbłasz, Sylwia; Raczyk, Andrzej (Quaestiones Geographicae, 2010)
Transborder co-operation is shaped by many factors and thus takes various forms on particular bor-ders. Within the same formal-legal arrangements under Interreg Programmes, the greatest role in the diver-sification of co-operation was played by non-system-related conditions specific to particular border regions. To identify what specifically drives co-operation, the nature of Polish-German and Polish-Czech transborder co-operation was compared. On the basis of the research conducted, it can be said that the existence of similar conditions on both sides of the border may define specific directions of co-operation and hence be called an inte-grating factor. Coupled with relatively weak barriers, this integrating factor may exert a powerful influence on the development and character of transborder co-operation. Thus, in the process of shaping co-operation policy it is crucial to identify the existing integrating factor (or to define the possibilities of creating it) and to limit the impact of co-operation barriers.